1977
DOI: 10.1159/000207802
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bleeding on <i>in vivo</i> and <i>in vitro</i> Colony-Forming Hemopoietic Cells

Abstract: The effect of bleeding on spleen colony-forming units (CFU-S) and on in vitro colony-forming cells with colony-stimulating factor (CFU-C) and erythropoietin (CFU-E) has been evaluated. The in vivo and in vitro colony-forming cells of the bone marrow show a decrease which for the CFU-E, CFU-C follows a shortlived increase. In the spleen, all progenitor cells assayed have shown a significant and sustained increase

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…5) presumably reflects a combination of several mechanisms. Splenectomy causes a loss of erythrocytes stored in the spleen and, in mice at least, a loss of active hemopoietic capacity (Brodsky et al, 1966;Pannacciuli et al, 1977). In addition, the capacity for removal of micronucleated erythrocytes by the reticuloendothelial system is probably temporarily reduced after splenectomy, since the spleen is known to selectively remove micronucleated red blood cells or micronuclei in some species (Crosby, 1959;Schalm, 1965).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5) presumably reflects a combination of several mechanisms. Splenectomy causes a loss of erythrocytes stored in the spleen and, in mice at least, a loss of active hemopoietic capacity (Brodsky et al, 1966;Pannacciuli et al, 1977). In addition, the capacity for removal of micronucleated erythrocytes by the reticuloendothelial system is probably temporarily reduced after splenectomy, since the spleen is known to selectively remove micronucleated red blood cells or micronuclei in some species (Crosby, 1959;Schalm, 1965).…”
Section: Discussionmentioning
confidence: 99%
“…Our data demonstrate that bleeding and phenylhydrazine-induced hemolysis generate an increase in micronucleated cells among the peripheral polychromatic and normochromatic erythrocytes of mice. In additon, it is shown that removal of the spleen, which is an active hemopoietic organ in mice (Brodsky et al, 1966;Pannacciuli et al, 1977), also causes a pronounced increase in micronucleated red blood cells in peripheral blood. Moreover, comparison of the micronucleus-inducing effect of cyclophosphamide in normal and splenectomized mice revealed no significant difference with regard to kinetics of formation and removal.…”
Section: Introductionmentioning
confidence: 99%
“…There is experimental evidence that recovery after bleeding in mice occurs within 8-10 days (Hara & Ogawa, 1977;Iscove, 1977;Pannaciulli, Massa & Saviane, 1977). The general course of recovery is shown in Fig.…”
Section: O D E L R E S U L T Smentioning
confidence: 94%
“…Experiments (Fig. 1) have demonstrated a marked variability in the response of the erythroid population to the same stimulus (bleeding to one third of original blood volume) (Hara Ogawa, 1977;Iscove, 1977;Pannaciulli et al, 1977). This variability is mainly due to the fact that the minimum value in erythrocyte kinetics occurs at different times.…”
Section: O D E L R E S U L T Smentioning
confidence: 96%
“…Further study has shown that these erythroid colonies contain at least two classes of stem cells, a more primitive erythroid burstforming unit (BFU-E) requiring long culture periods (10-14 days) with high erythropoietin levels and a more differentiated colony-forming unit-erythroid (CFU-E) requiring lower erythropoietin level and only 2 days of culture (23,33). Marrow CFU-E numbers follow a predictive pattern, increased following bleeding (34) and decreased during plethora induced by red cell transfusions (35). Erythroid progenitors as measured by clonal assays are sensitive to cytostatic agents (30,36,37) and known marrow toxicicants such as benzene (38,39).…”
Section: Erythroid Progenitors (Cfu-e Bfu-e)mentioning
confidence: 99%